2007
DOI: 10.1515/advgeom.2007.019
|View full text |Cite
|
Sign up to set email alerts
|

Painlevé equations and the middle convolution

Abstract: We use the middle convolution to obtain some old and new algebraic solutions of the Painlevé VI equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…And, Crawley-Boevey views the construction, again in algebraic terms, as something about root systems. Boalch considered a particular example of middle convolution in a non-rigid case [15], and the link with Katz's construction was made in [47]. In [45] following [86,Chap.…”
Section: Middle Convolution-betti Versionmentioning
confidence: 99%
See 2 more Smart Citations
“…And, Crawley-Boevey views the construction, again in algebraic terms, as something about root systems. Boalch considered a particular example of middle convolution in a non-rigid case [15], and the link with Katz's construction was made in [47]. In [45] following [86,Chap.…”
Section: Middle Convolution-betti Versionmentioning
confidence: 99%
“…Boalch considered a particular example of middle convolution in a non-rigid case [15], and the link with Katz's construction was made in [47]. In [45] following [86,Chap. 5.1] it is shown that the explicit matrix definition of M C has a geometric or cohomological interpretation as a higher direct image-this is the point of view we adopt here.…”
Section: Middle Convolution-betti Versionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dettweiler and Reiter's algebraic analogue [7,8] of Katz' middle convolution is a certain transformation of Fuchsian systems which preserves an index of rigidity. Middle convolution is related to the Euler transformation of the Fuchsian system.…”
Section: Middle Convolutionmentioning
confidence: 99%
“…We shall first review definitions of the Fuchsian system and its monodromy representation, formulate the Riemann-Hilbert problem and present some of the known methods of its constructive solutions (other methods and further references can be found in, for example, a survey paper [14]). Then we shall briefly describe an algorithm of middle convolution following [7,8] and, finally, we shall present our new approach (the general scheme) to constructive solutions of the Riemann-Hilbert problem via middle convolution with two illustrative examples.…”
Section: Introductionmentioning
confidence: 99%